Uji Antioksidan dan Antiradikal Bebas dari Ekstrak Kulit Buah Rambutan (Nephelium lappaceum L) Var Binjai - Yuyun, Yonelian (Media Eksakta, 2011)
The antioxidan test of rambutan (Nephelium lappaceum L.) var. Binjai rind extract was carried out by thin layer chromatography (TLC) using 0,05% β-carotene solution. Rambutan rind was extracted with maceration method using a mixture of methanol and concentrated HCl (99:1) as solvent. The TLC result with mobile phase of butanol-acetic acid glacial-water showed that spots with Rf value 0,51 dan 0,65 showed antioxidant and free radical scavenging properties. Observation with spectrophotometry showed that rambutan rind extract as free radical scavenger. The IC50 of rambutan rind extract as free radical scavenger was 97,763 µg/ml and rutin as the reference compound had IC50 4,530 µg/ml